A escola normal de Santos: uma realização da Associação Instrutiva José Bonifácio 1928-1933 - Nascimento, Lúcia Tavares (2016)
This Master¿s Thesis contains the research results related to the foundation of the educational school named ¿Associação Instrutiva José Bonifácio¿ in Santos (SP). With the enactment of the law 2.269/1927 (SP). It is limited between the years 1928, which is the year of foundation of free educational schools of the State of São Paulo, matched with the capital¿s oficial educational school, and 1933, year of the state¿s educational code promulgation. This reform is the consequence of the laws related to the public instruction, previously not allowed to the city halls and private people to act in the teaching area, previously dependent of the State. The raise in the number of schools had the goal to form new elementary teachers and to reduce the illiteracy in rural areas. The research methodology was the historical study of the teaching institution documents and the state¿s legislation. The establishment of an institution focused on the teacher¿s qualification and recognized by the State of São Paulo occurred previously in regions of lower political and economic expression, in comparison to Santos, and the creation of the free educational schools and the AIJB, professional's qualification school, contributed to the number raise of these professionals for the city of Santos, its region and the São Paulo state.